THE IMPORTANCE OF EMOTIONAL INTELLIGENCE IN INTERPERSONAL RELATIONSHIPS DURING ADOLESCENCE (Universal International Scientific Journal, 2026)
This article analyzes the importance of emotional intelligence in the developmentof interpersonal relationships during adolescence. Emotional intelligence refers to the ability of aperson to understand and manage their own emotions as well as recognize the emotions of others.Particularly during adolescence, this ability plays a significant role in social adaptation, effectivecommunication with peers, and personal development
Keywords: emotional intelligence; adolescence; interpersonal relationships